“Cada um brinca com o que quiser! Isso aí é rachismo!” : infância e relações de gênero na brinquedoteca de uma instituição de educação infantil - Camargo, Sandra Celso de (2019)
Discussing and problematizing, in institutions of Early Childhood Education, the relations of power which hierarchize and structure the masculinity and femininity, valuing the lives that matter and the ones that are not likely to be lived, is urgent and necessary. In the face of the raising of conservatism, which intends to eliminate the discussions related to difference, it is necessary to forge places where the debate may occur. These movements attribute, in pedagogical policies, the only way of seeing and living childhood. The adultcentrism relation, which puts the child in a place of coming-to-be, denying, therefore, its sexuality, controls ordinary actions. The discourse of protection masks the mechanism of power which scrutinizes childhood as a linear phase of life. The child is shaped for a two-way journey of life, controlled by heteronormativity. The current study is linked to the research group “Childhood, Youth and Contemporary Culture” (GEIJC), of the research line “Childhood, Youth and Contemporary Culture: rights, policies and diversity”, part of the Postgraduate Program in Education (PPGEdu), of the Federal University of Mato Grosso (UFMT), of the University Campus of Rondonópolis (CUR), Mato Grosso (MT). It has the main objective of analyzing the gender relations in the ways how children and teachers share the environment of the playroom and the meanings they make about these relations in the experiences lived in the institution of Early Childhood Education. More specifically, the following questions are raised: 1) How do girls and boys interact in the environment of the playroom, parting from the play which they arrange in this context and the meanings they produce about the gender relations that penetrate the shared experiences? 2) What meanings do the teachers attribute to the gender relations, shared in the environment of the playroom, considering the ways how this is organized by them, the objects chosen for this organization and the uses which the children make of this environment and of the objects in their play? As theoretical basis, we part from the studies of the childhood, understood as a historical and social category; the studies of gender, in an intercessional approach, and of the perspective of Foucault, in comprehending sexuality as a mechanism of power. The context of research is a Municipal Center of Early Childhood Education (CMEI), of the city of Rondonópolis, in Mato Grosso. In this research participated 22 children, age 5, of the second school group of the Second Cycle of Early Childhood Education, 19 teachers, two pedagogical coordinators and the principal of the institution. The methodological approach is outlined as an intervention research. The production of the data was conducted through the participant observation of the experiences and the relations between the children and of their interactions with the teacher in the playroom, of which the occurrences were recorded through notes in the field diary, photos, video recording and audio recording, and of semi structured interviews and yarning circles with the teachers, the pedagogical coordinators and the principal, based on the records made along the observations about what is lived in this place. The investigation was conducted through the feminist intercessional perspective and is based on the concepts of dialogism and alterity, as approached by Mikhail Bakhtin. The analyses are centered in the discourses which confirm the childhood, as moment of correction so that the deviations which conduct the ideal adult do not occur, and in the mechanisms of correction and control of the bodies of the children, which, from a matrix of intelligibility, have their sexuality precluded. In a more profound analysis, the Institution of Early Childhood Education, basing on the discourses of the psychology of development and of the traditional pedagogy, presents itself as a space of control of the bodies of girls and boys, guiding their doings though heteronormativity, but also is a space of resistance and transgressions. In the border, the crystalized norms are destabilized: the child is not passive to the norm, engenders other forms of existence in their plays and interactions.